Juvenile peripheral LPS exposure overrides female resilience to prenatal VPA effects on adult sociability in mice - Seiffe, Araceli (2024)
Autism spectrum disorder (ASD) exhibits a gender bias, with boys more frequently affected than girls. Similarly, in mouse models induced by prenatal exposure to valproic acid (VPA), males typically display reduced sociability, while females are less affected. Although both males and females exhibit VPA effects on neuroinflammatory parameters, these effects are sex-specific. Notably, females exposed to VPA show increased microglia and astrocyte density during the juvenile period. We hypothesized that these distinct neuroinflammatory patterns contribute to the resilience of females to VPA. To investigate this hypothesis, we treated juvenile animals with intraperitoneal bacterial lipopolysaccharides (LPS), a treatment known to elicit brain neuroinflammation. We thus evaluated the impact of juvenile LPS-induced inflammation on adult sociability and neuroinflammation in female mice prenatally exposed to VPA. Our results demonstrate that VPA-LPS females exhibit social deficits in adulthood, overriding the resilience observed in VPA-saline littermates. Repetitive behavior and anxiety levels were not affected by either treatment. We also evaluated whether the effect on sociability was accompanied by heightened neuroinflammation in the cerebellum and hippocampus. Surprisingly, we observed reduced astrocyte and microglia density in the cerebellum of VPA-LPS animals. These findings shed light on the complex interactions between prenatal insults, juvenile inflammatory stimuli, and sex-specific vulnerability in ASD-related social deficits, providing insights into potential therapeutic interventions for ASD.